PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR IPAS KELAS V DI SDN 88 PALEMBANG - Dwi Anjani, Imelda; Hakim, Lukman; Riyanti, Henni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) learning model on student learning outcomes in the subject of science on the human respiratory system of grade V students. The research method used is quantitative with a quasi-experimental design. The population in this study were all grade V of SD Negeri 88 Palembang. The sample of participants was taken using a random sampling technique and obtained 26 students of grade V.4 as an experimental class using the Project Based Learning (PjBL) learning model and 24 students of grade V.3 as a control class using conventional learning. Data collection techniques in this study were tests, documentation and observation. The data analysis technique used was the t-test. The results of the study obtained a value of 0.000 <0.05, which means that there is an effect of the project based learning (PjBL) learning model on the science learning outcomes of grade V SD Negeri 88 Palembang. Furthermore, the mean difference value or the difference in the average pretest and posttest in the experimental class was 45.654, while in the control class it was 44.833 which shows that the increase in learning outcomes of students in the experimental class was higher than in the control class.